DEM based examination of pediment levels: a case study in Bükkalja, Hungary - János Vágó (Hungarian Geographical Bulletin, 2011)
Bükkalja is the southern pediment of Bükk Mountains. According to the geographic literature this area is divided into two pediment (geomorphic) levels. Using the methods of quantitative geomorphology, the Bükkalja pilot area was examined in this paper. The main objectives of the investigation were the validation of examinations based on the digital elevation model by the accepted scientific achievements (referring to the dual pediment), and the analysis of the role of Miocene welded ignimbrite cuestas in the evolution of the pediment. Applying different GIS based methods, the height and location of these levels were determined and their area calculated as well. Relationship was established between the location of the upper pediment level and the occurrence of welded ignimbrites on the surface. The leading role of welded ignimbrite cuestas was also confirmed by the morphometric analysis of tuff formations.